High-orientation and high-compactness ceramic as well as preparation method and application thereof

By using the composite of high-oriented ceramic powder with small-particle and large-particle diameters and the use of graphene oxide aqueous solution in ceramic materials, combined with binding aids and vacuum suction filtration technology, the problems of poor orientation and low density of ceramic materials during sintering are solved, and the preparation of high-oriented and high-density ceramics is achieved, and its mechanical strength and thermal conductivity are improved.

CN119841625AActive Publication Date: 2025-04-18CHINA IRON & STEEL RESEARCH INSTITUTE GROUP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410640968.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-22
Publication Date
2025-04-18
Estimated Expiration
2044-05-22

AI Technical Summary

Technical Problem

During the sintering process, existing high-oriented structural ceramic materials have problems such as uneven stacking structure, poor orientation and low powder density, which leads to unstable performance, high porosity and many residual defects of the ceramic materials, which affects their mechanical properties and practicality.

Method used

Any two or more raw materials in small-particle high-oriented ceramic powder, large-particle high-oriented ceramic powder and graphene oxide aqueous solution are combined, and bonding aids are used to optimize the orientation and density of the ceramic by designing powder mixing methods, introducing graphene oxide and vacuum suction filtration methods.

Benefits of technology

It improves the high orientation and density of ceramic materials, improves its mechanical strength and thermal conductivity, reduces porosity and residual defects, and ensures the performance stability of ceramic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841625A_ABST
    Figure CN119841625A_ABST
Patent Text Reader

Abstract

The invention relates to high-orientation and high-compactness ceramic as well as a preparation method and application thereof, and belongs to the technical field of functional ceramic material preparation. The high-orientation and high-compactness ceramic is prepared from any two or more of a bonding aid, small-particle-size high-orientation ceramic powder, large-particle-size high-orientation ceramic powder and a graphene oxide aqueous solution. The small-particle-size high-orientation ceramic powder and the large-particle-size high-orientation ceramic powder are selected from alpha-Al2O3, hBN, SiC, layered molybdate and SiO2; the bonding aid is selected from yttrium oxide, magnesium oxide, aluminum oxide, silicon dioxide and mullite. Small-particle-size high-orientation ceramic powder and / or large-particle-size high-orientation ceramic powder are / is mixed with a graphene oxide aqueous solution, under the assistance of a bonding auxiliary agent, the particle size and weight ratio of the high-orientation ceramic powder are strictly regulated and controlled, gaps among the large-particle-size high-orientation ceramic powder are filled with small particles, and the high-orientation ceramic powder is prepared. The mechanical property and the functional property of the ceramic are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional ceramic material preparation, and in particular to a high-oriented and high-density ceramic and a preparation method and application thereof. Background Art

[0002] Highly oriented structural ceramics have a wide range of applications in modern industry and technology. These ceramic materials usually exhibit superior mechanical properties in a certain direction, which enables them to perform well when they need to withstand high stress in a specific direction or are used in functional structural components.

[0003] Although ceramic materials with highly oriented structures have important applications in many fields, there are still some problems in the actual preparation and sintering process, which limit their practical application. Highly oriented structural ceramic materials are usually made by pressing powders with high orientation (such as fibrous, columnar, and lamellar) into embryos and then sintering them. However, during the sintering process, the particle size of highly oriented powders has problems such as uneven stacking structure, poor orientation, and low powder density, which leads to the final ceramic material having unstable performance, high porosity, and many residual defects (such as pores, cracks, etc.), which in turn affects its mechanical properties and practicality. For example, the directional thermal conductivity of existing hexagonal boron nitride ceramics is far different from the in-plane thermal conductivity of its monolithic structure, mainly because the hexagonal boron nitride powder has a unique multi-layer lamellar structure and extremely high hardness. During the ceramic embryo molding and sintering process, it is very easy to form a "card room structure" with interlocking layers containing more pores, which affects the structural orientation, sintering density, and mechanical and machining properties of the ceramics.

[0004] In order to improve the orientation and density of ceramic materials, existing methods usually use sintering methods such as high temperature, high pressure, and discharge plasma, and combine ceramic grain orientation control methods such as magnetic field, liquid phase sintering, and template grain growth to achieve the purpose of optimizing the structural arrangement of the crystal grain size inside the ceramic during the ceramic sintering process. Although such methods can improve the structural orientation and mechanical, directional thermal and electrical conductivity of ceramic materials to a certain extent, they usually require complex and precise process control, and have high requirements for sintering temperature, pressure, atmosphere, etc. For example, some ceramic materials with oriented structures require higher sintering temperatures, but at high temperatures, they may cause grain growth, phase change or oxidation of the material, thereby affecting its performance. For example, the hot pressing sintering process can axially pressurize ceramic powders to improve the orientation of the material, but it is impossible to prepare ceramic materials with complex morphological structures. Due to the poor structural uniformity and poor density of the ceramic embryo itself, it is easy to cause the ceramic embryo structure to crack under sintering conditions such as high pressure and high temperature, affecting the preparation efficiency and performance stability of ceramic materials. Summary of the invention

[0005] In view of the above analysis, the present invention aims to provide a highly oriented and high-density ceramic and a preparation method and application thereof, so as to solve the problem of poor performance of existing ceramic materials.

[0006] On the one hand, the present invention provides a highly oriented and high-density ceramic, wherein the raw materials for preparing the ceramic include any two or more raw materials selected from small-particle-size highly oriented ceramic powder, large-particle-size highly oriented ceramic powder and graphene oxide aqueous solution, and a bonding aid;

[0007] The small-particle-size high-oriented ceramic powder and the large-particle-size high-oriented ceramic powder are selected from α-Al 2 O 3 , hBN, SiC, layered molybdates and SiO 2 ;

[0008] The bonding aid is selected from yttrium oxide, magnesium oxide, aluminum oxide, silicon dioxide and mullite.

[0009] Furthermore, the mass ratio of the small-particle-size high-oriented ceramic powder and / or the large-particle-size high-oriented ceramic powder to the bonding aid is 100:(0-40).

[0010] Furthermore, the mass ratio of the small-particle high-oriented ceramic powder and / or the large-particle high-oriented ceramic powder to the graphene oxide aqueous solution is 10:1-200:1.

[0011] Furthermore, the mass ratio of the large-particle-size high-oriented ceramic powder to the small-particle-size high-oriented ceramic powder is 1:1-1:35.

[0012] Furthermore, the average particle size of the large-particle high-oriented ceramic powder is 80-500 μm; the average particle size of the large-particle high-oriented ceramic powder is 10-30 times the average particle size of the small-particle high-oriented ceramic powder.

[0013] Furthermore, the particle size of the bonding aid is smaller than or equal to the average particle size of the small-particle-size and highly-oriented ceramic powder.

[0014] In another aspect, the present invention provides a method for preparing a highly oriented and highly dense ceramic, comprising the following steps:

[0015] S1: Weigh large-particle-size high-oriented ceramic powder and small-particle-size high-oriented ceramic powder according to proportion and mix them with solvent respectively, with the mixing ratio being 10g:1L;

[0016] Then, any two or more of the mixed large-particle-size high-oriented ceramic powder solution, small-particle-size high-oriented ceramic powder solution and graphene oxide aqueous solution are mixed;

[0017] S2: Weigh the bonding agent according to the proportion and mix it with the solvent, the mixing ratio is 10g:1L;

[0018] S3: Mix the mixed solution prepared in S1 and S2, stir, and then use vacuum filtration to obtain a dry mixed powder block, and transfer the mixed powder block to a sintering mold;

[0019] S4: placing the mold in a heating furnace and drying it at 100-600° C. for 0.5-2 hours to obtain a ceramic green body;

[0020] S5: Sintering the obtained ceramic green body to obtain a highly oriented and high-density ceramic.

[0021] Furthermore, the diameter of graphene oxide sheets in the graphene oxide aqueous solution is ≥5 μm.

[0022] Furthermore, the present invention provides an application of a highly oriented and high-density ceramic in the preparation of a directional heat-isolating composite honeycomb structure, wherein the directional heat-isolating composite honeycomb structure comprises an outermost directional heat-isolating layer, and the directional heat-isolating layer is prepared using the highly oriented and high-density ceramic described in the present invention.

[0023] Furthermore, a directional heat-averaging composite honeycomb structure comprises, from top to bottom, a directional heat-averaging layer, an upper skin, a honeycomb core, a core filler and a lower skin, wherein the directional heat-averaging layer is prepared using the highly oriented and high-density ceramic obtained by the present invention.

[0024] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0025] 1. The high-orientation and high-density ceramics provided by the present invention adopt any two or more raw materials of small-particle high-oriented ceramic powder, large-particle high-oriented ceramic powder and graphene oxide aqueous solution, such as a compound of small-particle high-oriented ceramic powder and large-particle high-oriented ceramic powder, or a compound of small-particle high-oriented ceramic powder and graphene oxide aqueous solution, or a compound of large-particle high-oriented ceramic powder and graphene oxide aqueous solution, or a compound of large-particle high-oriented ceramic powder, small-particle high-oriented ceramic powder and graphene oxide aqueous solution; finally, a bonding agent is added to improve the orientation and density of the green embryo structure during the molding process, so as to enhance the high orientation and excellent performance of the ceramic material finally obtained.

[0026] 2. The present invention adopts a compound of small-particle high-oriented ceramic powder and large-particle high-oriented ceramic powder, and controls the ratio between the two, and selects high-oriented ceramic powders with different orientation forms (such as fibrous, columnar, and lamellar) and different particle sizes, so as to obtain highly oriented and high-density ceramics with higher density and mechanical strength.

[0027] 3. The present invention uses small-particle high-oriented ceramic powder or large-particle high-oriented ceramic powder and mixes it with graphene oxide aqueous solution, which can optimize the orientation and performance of the ceramic.

[0028] 4. The present invention adopts small-particle high-oriented ceramic powder and large-particle high-oriented ceramic powder and mixes them with graphene oxide aqueous solution, and with the assistance of bonding additives, strictly controls the particle size and weight ratio of high-oriented ceramic particles, and fills the gaps between large-particle high-oriented ceramic powders with small particles, thereby improving the density of ceramics; utilizes the orientation preference of large-particle high-oriented ceramic powders in the stacking process to optimize the orientation of ceramics, and large-particle high-oriented ceramic powders act as a "structural bridge" between small-particle high-oriented ceramic powders and bonding additives, greatly improving the mechanical strength of ceramics.

[0029] 5. The preparation method of the ceramic of the present invention further optimizes the orientation of the mixed powder during the drying process by designing a powder mixing method, introducing graphene oxide and vacuum filtration. The highly oriented ceramics prepared by this method have a lower porosity than ceramics prepared by traditional methods, and can still show excellent material properties even under pressureless sintering conditions, such as ultra-high in-plane thermal conductivity and ultra-high bending strength.

[0030] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The drawings are only for the purpose of illustrating specific embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0032] Figure 1 This is a scanning electron microscope photograph of the ceramic fracture obtained in Example 11;

[0033] Figure 2 This is a scanning electron microscope photograph of the ceramic fracture obtained in Example 10;

[0034] Figure 3 This is a scanning electron microscope photograph of the ceramic fracture obtained in Example 9;

[0035] Figure 4 This is a scanning electron microscope photograph of the ceramic fracture obtained in Example 12;

[0036] Figure 5 This is a scanning electron microscope photograph of the ceramic fracture obtained in Example 15;

[0037] Figure 6 This is a scanning electron microscope photograph of the ceramic fracture obtained in Example 16;

[0038] Figure 7 It is a directional and heat-homogenizing composite honeycomb structure;

[0039] Among them, 11, upper skin; 12, lower skin; 2, honeycomb core; 3, directional heat-isolating layer; 4, core filling. DETAILED DESCRIPTION

[0040] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0041] Highly oriented structural ceramics are becoming more and more popular due to their superior mechanical and functional properties. However, highly oriented structural ceramics are usually made by pressing powders with high orientation (such as fibrous, columnar, and lamellar) into a green body and then sintering it. However, during the sintering process, highly oriented powders have problems such as uneven stacking structure, poor orientation, and low powder density, resulting in unstable performance, high porosity, and more residual defects (such as pores, cracks, etc.) in the final ceramic material, which in turn affects its mechanical properties and practicality.

[0042] Therefore, the present invention provides a high-orientation and high-density ceramic, the preparation raw materials include any two or more raw materials of small-particle-size high-orientation ceramic powder, large-particle-size high-orientation ceramic powder and graphene oxide aqueous solution, and a bonding aid;

[0043] The small-particle-size high-oriented ceramic powder and the large-particle-size high-oriented ceramic powder are selected from α-Al 2 O 3 , hBN, SiC, layered molybdates and SiO 2 ;

[0044] The bonding aids include yttrium oxide, magnesium oxide, aluminum oxide, silicon dioxide and mullite.

[0045] Compared with the prior art, the high-orientation and high-density ceramics provided by the present invention adopt any two or more raw materials of small-particle high-oriented ceramic powder, large-particle high-oriented ceramic powder and graphene oxide aqueous solution, such as a compound of small-particle high-oriented ceramic powder and large-particle high-oriented ceramic powder, or a compound of small-particle high-oriented ceramic powder and graphene oxide aqueous solution, or a compound of large-particle high-oriented ceramic powder and graphene oxide aqueous solution, or a compound of large-particle high-oriented ceramic powder, small-particle high-oriented ceramic powder and graphene oxide aqueous solution; finally, a bonding agent is added to improve the orientation and density of the green embryo structure during the molding process, so as to enhance the high orientation and excellent performance of the ceramic material finally obtained.

[0046] It should be noted that the small-particle high-orientation ceramic powder and large-particle high-orientation ceramic powder of the present invention are selected from materials with orientation, such as one-dimensional fiber or rod; two-dimensional lamellar. For example, lamellar α-Al 2 O 3 , lamellar hexagonal boron nitride (hBN), etc.

[0047] Specifically, the mass ratio of the small-particle high-oriented ceramic powder and / or the large-particle high-oriented ceramic powder to the bonding aid is 100:(0-40), such as 100:1, 100:10, 100:20, 100:30 or 100:40.

[0048] It should be noted that the bonding aid in the present invention is used in combination with highly oriented ceramic powder to prepare ceramics, and the type of bonding aid affects the properties of the final ceramics. When the bonding aid is selected as alumina, the resulting ceramics have higher thermal conductivity; when the bonding aid is selected as mullite, the resulting ceramics have higher hardness; when the bonding aid is selected as a mixture of alumina, magnesium oxide and mullite, the resulting ceramics have both better thermal conductivity and higher mechanical strength.

[0049] The present invention can select different bonding aids according to different usage scenarios of the ceramics, such as usage scenarios with high thermal conductivity requirements and low mechanical property requirements; or high thermal conductivity and mechanical property requirements; or high mechanical property requirements and low thermal conductivity. The overall solution is simple and relatively flexible.

[0050] Furthermore, the mass ratio of the small-particle highly oriented ceramic powder and / or the large-particle highly oriented ceramic powder to the graphene oxide aqueous solution is 10:1-200:1, such as 10:1, 20:1, 40:1, 50:1, 70:1, 80:1, 100:1, 120:1, 150:1, 180:1 or 200:1.

[0051] Specifically, the diameter of the graphene oxide sheets in the graphene oxide aqueous solution is ≥5 μm.

[0052] Specifically, the concentration of the graphene oxide aqueous solution is 0.5 mg / ml-10 mg / ml, such as 0.5 mg / ml, 1.5 mg / ml, 2.5 mg / ml, 5 mg / ml, 7 mg / ml or 10 mg / ml.

[0053] It should be noted that during the preparation of ceramics, an aqueous solution of graphene oxide (GO solution for short) was added, which can reduce the repulsive force between particles caused by cohesive force between small particles of highly oriented ceramic powder, optimize its arrangement structure, and make the highly oriented ceramic powder and the bonding agent more evenly dispersed. Combined with vacuum filtration, the surface structure of the resulting ceramic is smoother, especially for boron nitride ceramics.

[0054] When the mass of highly oriented ceramic powder is less than 10 times the mass of graphene oxide, the graphene content is too high, affecting the material's temperature resistance; when the mass of highly oriented ceramic powder is higher than 200 times the mass of graphene oxide, the graphene content is too low and cannot play a role in regulating the ceramic arrangement structure and optimizing the structural mechanical properties.

[0055] Specifically, the average particle size of the large-particle-size high-oriented ceramic powder is 10-30 times the average particle size of the small-particle-size high-oriented ceramic powder.

[0056] Specifically, the average particle size of the large-particle-size and highly-oriented ceramic powder is 80-500 μm.

[0057] It should be noted that in the present invention, large-particle high-oriented ceramic powder and small-particle high-oriented ceramic powder can be compounded, and the particle size and weight ratio of large-particle high-oriented ceramic powder and small-particle high-oriented ceramic powder can be further controlled and optimized. The small-particle high-oriented ceramic powder is used to fill the gaps between the large-particle high-oriented ceramic powders, thereby improving the density of the ceramics. The orientation preference of the large-particle high-oriented ceramic powder during the stacking process is utilized to optimize the orientation of the ceramics, and the large-particle high-oriented ceramic powder can act as a "structural bridge" between the small-particle high-oriented ceramic powder and the bonding aid, greatly improving the mechanical strength of the ceramics.

[0058] Specifically, the mass ratio of the large-particle-size high-oriented ceramic powder to the small-particle-size high-oriented ceramic powder is 1:1-1:35.

[0059] Preferably, the average particle size of the large-particle-size and highly-oriented ceramic powder may be 80 μm, 120 μm, 200 μm, 350 μm or 500 μm.

[0060] Preferably, the average particle size of the small-particle-size and highly-oriented ceramic powder may be 2 μm, 8 μm, 12 μm, 25 μm or 50 μm.

[0061] The present invention needs to regulate the mass ratio of large-particle-size high-oriented ceramic powder and small-particle-size high-oriented ceramic powder, and control the mass of small-particle-size high-oriented ceramic powder to be 1-35 times that of large-particle-size high-oriented ceramic powder.

[0062] Preferably, the mass of the small-particle highly oriented ceramic powder is 1 times, 2 times, 4 times, 6 times, 10 times, 15 times, 18 times, 22 times, 25 times, 30 times or 35 times that of the large-particle highly oriented ceramic powder.

[0063] Preferably, the mass of the small-particle-size highly-oriented ceramic powder is 1-10 times that of the large-particle-size highly-oriented ceramic powder.

[0064] According to simulation and experimental results, as the content of large-particle-size, highly oriented ceramic powder decreases, the resulting orientation gradually decreases. The larger the absolute value of IOP, the higher the orientation of the material.

[0065] Specifically, the bonding aids include yttrium oxide, magnesium oxide, aluminum oxide, silicon dioxide and mullite.

[0066] Specifically, the particle size of the bonding aid is smaller than or equal to the average particle size of the selected small-particle-size and highly-oriented ceramic powder.

[0067] It should be noted that the large-particle-size high-oriented ceramic powder in the present invention serves as a bridge connecting the small-particle-size high-oriented ceramic powder and the bonding agent, and the bonding agent particle size is regulated to be less than or equal to the average particle size of the small-particle-size high-oriented ceramic powder. When the bonding agent particle size is small, it can fill in the gaps and increase the density and strength of the final ceramic.

[0068] The present invention provides a method for preparing a highly oriented and highly dense ceramic, comprising the following steps:

[0069] S1: Weigh large-particle-size high-oriented ceramic powder and small-particle-size high-oriented ceramic powder according to proportion and mix them with solvent respectively, with the mixing ratio being 10g:1L;

[0070] Then, any two or more of the mixed large-particle-size high-oriented ceramic powder solution, small-particle-size high-oriented ceramic powder solution and graphene oxide aqueous solution are mixed;

[0071] S2: Weigh the bonding agent according to the proportion and mix it with the solvent, the mixing ratio is 10g:1L;

[0072] S3: Mix the mixed solution prepared in S1 and S2, stir, and then use vacuum filtration to obtain a dry mixed powder block, and transfer the mixed powder block to a sintering mold;

[0073] S4: placing the mold in a heating furnace and drying it at 100-600° C. for 0.5-2 hours to obtain a ceramic green body;

[0074] S5: Sintering the obtained ceramic green body to obtain a highly oriented and high-density ceramic.

[0075] Compared with the prior art, the present invention adopts a compound of large-particle-size high-oriented ceramic powder and small-particle-size high-oriented ceramic powder, which can improve the orientation of ceramic green body and final ceramic; or add graphene oxide aqueous solution to large-particle-size high-oriented ceramic powder and / or small-particle-size high-oriented ceramic powder, and cooperate with vacuum filtration means, which can improve the orientation and performance of ceramic green body and final ceramic.

[0076] Before sintering, the mixed powder block needs to be dried at 100-600°C. When graphene oxide aqueous solution is used, it is dried at 100-500°C in order not to affect the material content. However, when there is residual graphene oxide aqueous solution during the preparation process, it is dried at 500-600°C for 0.5-1h. Graphene will undergo aerobic oxidation in an environment above 500°C, converted into carbon dioxide and discharged, and the residual graphene oxide is removed.

[0077] By adopting the preparation method of the ceramic of the present invention, the porosity of the obtained ceramic green body is lower than that of the ceramic powder green body prepared by the traditional method (pressing), and the obtained ceramic still has excellent properties even under pressureless sintering conditions, such as ultra-high in-plane thermal conductivity, ultra-high bending strength, etc. For example, when preparing alumina ceramics, the bending strength is above 190.67MPa; when preparing hexagonal boron nitride ceramics, the axial thermal conductivity is above 12.05W / m·K, and the radial thermal conductivity is above 90.22W / m·K.

[0078] Specifically, the solvent includes, but is not limited to, one or more of water, methanol, ethanol, ethylene glycol, isopropanol, butylpentane, dimethylformamide, acetone, and tetrahydrofuran.

[0079] It should be noted that adding a solvent to the large-particle high-oriented ceramic powder and / or the small-particle high-oriented ceramic powder in the present invention can make them disperse better without causing agglomeration problems. For example, hBN disperses better in isopropanol than in water.

[0080] Specifically, in step S6, the sintering is performed by pressure sintering or pressureless sintering, and the sintering temperature is 1750-2000°C.

[0081] Specifically, during pressure sintering, the pressure is 5MPa-40MPa.

[0082] The present invention also provides an application of a ceramic for preparing a directional heat-isolating composite honeycomb structure, wherein the directional heat-isolating composite honeycomb structure comprises, from top to bottom, a directional heat-isolating layer, an upper skin, a honeycomb core and core filler, and a lower skin; wherein the directional heat-isolating layer is prepared by the ceramic of the present invention.

[0083] It should be noted that on the basis of a single honeycomb structure, a directional heat-averaging layer is added to the surface. This structure can conduct heat laterally to the low temperature area, thus avoiding the gathering and accumulation of heat on the surface to a great extent, reducing the input of effective heat per unit area in the heat concentration area on the honeycomb surface, making the surface energy distribution more uniform, and hindering part of the heat from being conducted to the inside of the honeycomb. It effectively solves the problem of severe local heating caused by insufficient heat resistance of the honeycomb structure in actual application, thereby effectively improving the thermal stability of the honeycomb structure.

[0084] Specifically, the thickness of the oriented heat-absorbing layer is 0.01 to 10 mm.

[0085] Specifically, the material of the upper skin and the lower skin is one of titanium-based and nickel-based alloys, and the thickness is 0.1 mm to 20 mm.

[0086] Specifically, the honeycomb core is a honeycomb-like grid structure with a thickness of 0.01 to 3 mm, a height of 1 to 50 mm, and is made of titanium alloy.

[0087] Specifically, the core filler has a density less than 1g / cm 3 One of the silicon-based fibers, silicon-based aerogels or graphene aerogels.

[0088] Specifically, the method for manufacturing a directional heat-saturated composite honeycomb structure comprises the following steps:

[0089] S1. Perform surface treatment by laying, spraying or brushing one or more layers of brazing material on the lower skin;

[0090] S2. Use vacuum brazing or gas shielded brazing to first weld the honeycomb core and the lower skin together;

[0091] S3, filling the honeycomb core filler into the honeycomb core mechanically and / or manually;

[0092] S4. Performing surface treatment by laying, spraying or brushing one or more layers of brazing material on the upper skin;

[0093] S5, welding the upper skin and the honeycomb core together to obtain a honeycomb structure; the welding temperature is 450-1400° C., and the insulation time is 20-60 min;

[0094] S6. Prepare a directional heat-saturating layer on the outer surface of the honeycomb structure upper skin by spraying, brazing or bonding;

[0095] S7. After the final welding of the components is completed, the whole is subjected to stabilization heat treatment, and the heat treatment temperature is 20 to 100°C lower than the welding temperature.

[0096] The directional heat-averaging honeycomb structure described in the present invention has an outermost directional heat-averaging layer that can avoid the aggregation and accumulation of heat on the surface to a great extent, and conduct the heat laterally to the low temperature area, thereby reducing the effective heat input per unit area in the heat concentration area on the honeycomb surface; the core filling inside the honeycomb can effectively hinder the transmission of heat inside the honeycomb through conduction and radiation effects, thereby improving the thermal capacity of the honeycomb structure, thereby reducing the effective transmission amount of honeycomb heat from the hot end to the cold end, and can effectively achieve secondary control of the introduced heat, thereby avoiding the problem of overheating failure of the protected device due to excessive introduced heat.

[0097] The use of the directional heat-homogenizing honeycomb structure of the present invention not only meets the current development trend of lightweighting, but also can effectively improve the heat resistance / insulation capacity of the honeycomb structure and the safety of the protected devices inside the honeycomb. It has the advantages of light weight, heat resistance and high insulation capacity.

[0098] In order to more clearly describe the present invention, it is further illustrated by the following examples and comparative examples.

[0099] Example 1

[0100] A kind of Al with high bending strength 2 O 3 The method for preparing ceramics comprises the following steps:

[0101] S1. Weigh large-size flake α-Al in proportion. 2 O 3 Ceramic powder (average particle size 80 μm) and small-particle flake α-Al 2 O 3 10 g of each ceramic powder (average particle size of 6 μm) was mixed with the solvent and mechanically stirred for 1 hour by adding 2 L of isopropanol;

[0102] S2. Weigh 20 ml of graphene oxide (GO) aqueous solution (5 mg / ml) and mix with the solution prepared in S1, and stir mechanically for 1 hour;

[0103] S3. Weigh the bonding agent Al according to the proportion 2 O 3 2 g of round powder (average particle size 2.5 μm) was mechanically stirred in 200 ml of isopropanol solution for 1 hour.

[0104] S4. The mixed solution prepared by S2 and S3 was mixed and mechanically stirred for 2 hours, and then a dry mixed powder block was obtained by vacuum filtration, and the mixed powder block was transferred to a sintering mold;

[0105] S5. The mold was placed in a muffle furnace and dried at 550 ° C for 2 hours under air atmosphere to obtain a ceramic green embryo;

[0106] S6. The obtained ceramic green body is sintered without pressure at a sintering temperature of 1850° C. for 12 h to obtain alumina ceramics.

[0107] Examples 2-8, Comparative Examples 1-2

[0108] The differences between Examples 2-8, Comparative Examples 1-2 and Example 1 are shown in Table 1, and the alumina ceramics obtained from Examples 1-8 and Comparative Examples 1-2 were subjected to performance tests, and the test results are shown in Table 2.

[0109] Table 1 Parameters of Examples and Comparative Examples

[0110] Group Large particle size / g Small particle size / g GO solution / ml Example 1 10 10 20 Example 2 6 14 20 Example 3 3 17 20 Example 4 0 20 20 Example 5 10 10 80 Example 6 10 10 200 Example 7 10 10 0 Example 8 20 0 20 Comparative Example 1 0 20 0 Comparative Example 2 20 0 0

[0111] Table 2 Test results

[0112]

[0113] It can be seen from Examples 1-4 in combination with Table 2 that by compounding large-particle high-oriented ceramic powder and small-particle high-oriented ceramic powder and adding graphene oxide aqueous solution, the absolute value of IOP and flexural strength of the obtained alumina ceramic are higher and the apparent porosity is lower, indicating that the obtained alumina ceramic has good orientation, strength and density.

[0114] It can be seen from Example 1 and Example 7, Example 4 and Comparative Example 1, and Example 8 and Comparative Example 2 in combination with Table 2 that when the graphene oxide aqueous solution is added to the large-particle-size highly oriented ceramic powder and / or the small-particle-size highly oriented ceramic powder, the IOP and flexural strength of the obtained alumina ceramic gradually increase, and the apparent porosity gradually decreases. This indicates that under the action of the graphene oxide aqueous solution, the orientation, strength and density of the alumina ceramic can be improved.

[0115] Example 9

[0116] A method for preparing highly oriented hexagonal boron nitride ceramics comprises the following steps:

[0117] Weigh 8 g of large-particle flaky hexagonal boron nitride ceramic powder (average particle size of 250 μm) and 12 g of small-particle flaky hexagonal boron nitride ceramic powder (average particle size of 10 μm) in proportion; a total of 20 g of oriented ceramic powder was added to 2 L of ethanol and mechanically stirred for 1 hour;

[0118] 40 ml of graphene oxide (GO) aqueous solution (5 mg / ml) was added, and mechanical stirring was continued for 2 hours.

[0119] The mixed solution was vacuum filtered to obtain a dry mixed powder block, which was transferred to a sintering mold. The mold was placed in a muffle furnace and dried at 550°C for 2 hours under air atmosphere to obtain a boron nitride ceramic green body, which was then hot-pressed and sintered (1900°C, 30MPa, 1h) to obtain hexagonal boron nitride ceramics.

[0120] Examples 10-18, Comparative Examples 3-4

[0121] The differences between Examples 10-18, Comparative Examples 3-4 and Example 9 are shown in Table 3. The hexagonal boron nitride ceramics obtained from Examples 9-18 and Comparative Examples 3-4 were tested for performance, and the test results are shown in Table 4.

[0122] Table 3 Parameters of Examples and Comparative Examples

[0123] Group Large particle size / g Small particle size / g GO solution / ml Example 9 8 12 0 Example 10 4 16 0 Embodiment 11 2 18 0 Example 12 8 12 40 Embodiment 13 4 16 40 Embodiment 14 2 18 40 Embodiment 15 8 12 80 Example 16 8 12 200 Embodiment 17 0 20 40 Embodiment 18 20 0 40 Comparative Example 3 0 20 0 Comparative Example 4 20 0 0

[0124] Table 4 Test results

[0125]

[0126]

[0127] It can be seen from Examples 9-14 and Table 4 that when a graphene oxide aqueous solution is added to a large-particle-size highly oriented ceramic powder and / or a small-particle-size highly oriented ceramic powder, the IOP and thermal conductivity of the obtained hexagonal boron nitride ceramic increase, and the density gradually increases. This indicates that under the action of the graphene oxide aqueous solution, the orientation, thermal conductivity and density of the hexagonal boron nitride ceramic can be improved.

[0128] Through Examples 9-11 and combined Figure 1-3 It can be seen that when GO solution is not added, as the content of large pieces increases, the orientation arrangement structure of hexagonal boron nitride ceramics is optimized.

[0129] By combining Examples 9, 12, 15, and 16 Figure 3-6 It can be seen that when the weight of large-particle high-oriented ceramic powder and small-particle high-oriented ceramic powder remains unchanged, the orientation arrangement structure of hexagonal boron nitride ceramics is optimized with the increase of GO solution content.

[0130] Application Examples

[0131] The above Example 12 was used to prepare a directional heat-isolation composite honeycomb structure. Figure 7 , from top to bottom, it includes a directional heat-averaging layer, an upper skin, a honeycomb core and core filler, and a lower skin; wherein the directional heat-averaging layer is prepared using the hexagonal boron nitride ceramic obtained in Example 12 of the present invention.

[0132] Application Example 1

[0133] Use 1000# sandpaper to grind the lower skin and one side of the honeycomb core to control the roughness within the range of 0.4-0.6, then spread the brazing material between the two. The brazing material is Ti-Zr-Cu-Ni. The welding is completed under vacuum conditions. The welding process is selected at 920℃ and the holding time is 20min. Then, the stabilization heat treatment is carried out at 900℃ and the holding time is 20min. The adjusted density is 0.8g / cm 3 The silica fiber is filled into the honeycomb core, the height of the honeycomb core is 10mm, the length of the silica fiber is 10.5mm, and the diameter is 20μm. Next, the same welding process as the lower skin is used to complete the welding with the upper skin. The adjusted high-temperature resistant inorganic glue is evenly applied between the TA15 panel and the hexagonal boron nitride ceramic with a thickness of 0.1mm. First, place it at room temperature for 2h, then keep it at 60℃ for 1h, and then continue to keep it at 100℃ for 2h to complete the bonding. Finally, the whole is kept at 150℃ for 10min for stabilization.

[0134] A directional heat-averaging composite honeycomb structure of a directional heat-averaging layer 3, an upper skin 11, a lower skin 12, a honeycomb core 2, and a core filler 4 is obtained, wherein the directional heat-averaging layer 3 has a thickness of 0.1 mm, the thicknesses of the upper skin 11 and the lower skin 12 are both 1 mm, the dimensions of the honeycomb core 2 are 10 mm in height and 10 mm in diameter of the inscribed circle, and the filling amount of the core filler 4 is filled by volume according to the specific density.

[0135] Back temperature test: One side of the honeycomb surface of the directional heat-absorbing layer was heated to 700°C, and the temperature of the other side was tested. The results showed that the measured cold surface temperature was lower than 60°C, which has better heat resistance.

[0136] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A highly oriented and high-density ceramic, characterized in that: The preparation raw materials include any two or more raw materials of small-particle high-oriented ceramic powder, large-particle high-oriented ceramic powder and graphene oxide aqueous solution, and a bonding aid; wherein the small-particle-size high-oriented ceramic powder and the large-particle-size high-oriented ceramic powder are selected from α-Al2O3, hBN, SiC, layered molybdate and SiO2; The bonding aid is selected from yttrium oxide, magnesium oxide, aluminum oxide, silicon dioxide and mullite.

2. The highly oriented and high-density ceramic according to claim 1, characterized in that: The mass ratio of the small-particle-size high-oriented ceramic powder and / or the large-particle-size high-oriented ceramic powder to the bonding aid is 100:(0-40).

3. The highly oriented and highly dense ceramic according to claim 1, characterized in that: The mass ratio of the small-particle high-oriented ceramic powder and / or the large-particle high-oriented ceramic powder to the graphene oxide aqueous solution is 10:1-200:

1.

4. The highly oriented and highly dense ceramic according to claim 1, characterized in that: The mass ratio of the large-particle-size high-oriented ceramic powder to the small-particle-size high-oriented ceramic powder is 1:1-1:

35.

5. The highly oriented and highly dense ceramic according to claim 1, characterized in that: The average particle size of the large-particle-size high-oriented ceramic powder is 80-500 μm; the average particle size of the large-particle-size high-oriented ceramic powder is 10-30 times the average particle size of the small-particle-size high-oriented ceramic powder.

6. The highly oriented and highly dense ceramic according to claim 1, characterized in that: The particle size of the bonding aid is smaller than or equal to the average particle size of the small-particle-size and highly-oriented ceramic powder.

7. A method for preparing a highly oriented and high-density ceramic according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: Weigh large-particle-size high-oriented ceramic powder and small-particle-size high-oriented ceramic powder according to proportion and mix them with solvent respectively, with the mixing ratio being 10g:1L; Then, any two or more of the mixed large-particle-size high-oriented ceramic powder solution, small-particle-size high-oriented ceramic powder solution and graphene oxide aqueous solution are mixed; S2: Weigh the bonding agent according to the proportion and mix it with the solvent, the mixing ratio is 10g:1L; S3: Mix the mixed solution prepared in S1 and S2, stir, and then use vacuum filtration to obtain a dry mixed powder block, and transfer the mixed powder block to a sintering mold; S4: placing the mold in a heating furnace and drying it at 100-600° C. for 0.5-2 hours to obtain a ceramic green body; S5: Sintering the obtained ceramic green body to obtain a highly oriented and high-density ceramic.

8. The method for preparing highly oriented and highly dense ceramics according to claim 7, characterized in that: The diameter of the graphene oxide sheets in the graphene oxide aqueous solution is ≥5 μm.

9. Application of a highly oriented and high-density ceramic in the preparation of an oriented and uniformly heated composite honeycomb structure, characterized in that: The oriented heat-averaging composite honeycomb structure comprises an outermost oriented heat-averaging layer, and the oriented heat-averaging layer is prepared by using the high-oriented and high-density ceramic according to any one of claims 1 to 6 or the high-oriented and high-density ceramic obtained according to claim 7 or 8.

10. A directional heat-isolating composite honeycomb structure, characterized in that: From top to bottom, there are oriented heat-averaging layer, upper skin, honeycomb core, core filler and lower skin. The oriented heat-averaging layer is made of the high-oriented and high-density ceramics described in any one of claims 1-6 or the high-oriented and high-density ceramics obtained in any one of claims 7 or 8.

Citation Information

Patent Citations

  • Ceramic-metal bionic nanocomposite material and preparation method thereof

    CN113277851A

  • Satellite-borne temperature control and installation integrated plate based on thermoelectric effect

    CN114275196A

  • Heat-resistant honeycomb structure and method of producing the same

    GB1439840A

  • Production of silicon carbide having high toughness

    JP1999079845A

  • Method for producing oriented ceramic sintered compact

    JP2018016505A